Determinants of human resource investment in internal controls - Jong-Hag Choi; Joonil Lee; Catherine Heyjung Sonu (China Journal of Accounting Research, 2013)
Using the unique reporting environment in Korea, this study investigates the determinants of human resource investment in internal controls for 1352 listed firms disclosing the number of personnel who are in charge of internal control-related tasks (IC personnel) from 2005 to 2008. We find that the number of IC personnel within a firm and several key departments increase with firm size, number of employees, complexity and for Chaebols, and decrease in rapidly growing firms. Additional analysis reveals that the factors influencing internal control systems have an accentuated effect on firms with relatively larger firm size.
Keywords: 650; Internal control personnel; Internal control systems; Internal control weaknesses